Politeness Strategies Used by Japanese and Indonesian Speakers on Social Media - Hani Sarila; Nuria Haristiani; Susi Widianti (Universitas Negeri Semarang, 2023)
This study compares the politeness strategies used by Japanese and Indonesian speakers in communication on social media, based on Brown and Levinson's (1987) politeness theory. To investigate the utilization of politeness strategies in social media interactions, we gathered 200 comments on several contents by public figures on Twitter and Instagram posted in December 2022. The dataset comprises 100 comments from Japanese users derived from posts made by accounts like @yousuck2020, @kishida230, @watanabenaomi703, and @yuriko.koike. The other 100 comments were collected from Indonesian users, originating from accounts such as @fiersabesari, @jokowi, @raffinagita1717, and @ridwankamil. The research findings show a similarity between Japanese and Indonesian speakers, with positive politeness strategy being the most frequently used politeness strategy in social media interactions. This is because there is a common desire to maintain good relationships in communication on social media. On the other hand, differences were observed in the utilization of negative politeness and off-record strategies. The research results reveal that the frequency of negative politeness strategies used by Japanese speakers was slightly higher than that used by Indonesian speakers. In comparison, the frequency of the off-record strategy was lower.